2022
DOI: 10.1177/13623613221111310
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between alexithymia, interoception, and emotional empathy in autism spectrum disorder

Abstract: Some studies suggest that individuals with autism spectrum disorder have reduced emotional empathy while others do not. The presence of co-occurring alexithymia in autism spectrum disorder and differences in interoception have been associated with reductions in empathic ability. To fully explore the relationships between interoception, alexithymia, and emotional empathy, we collected self-report and interview data in 35 youth with autism spectrum disorder and 40 typically developing controls (ages 8–17 years).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 111 publications
8
20
0
Order By: Relevance
“…Personal distress is often considered a maladaptive empathy response associated with depression, rumination, and negative self-image [ 73 , 129 ], and increased personal distress in ASD is consistent with a prior study from our group with lower sample sizes [ 73 ]. As we have already discussed the nuances of empathy in ASD in our previous paper (interactions with alexithymia and interoceptive processing being key modulators to empathy in ASD) [ 73 ], we do not expand on this finding here, only noting that our results here do not show support for cognitive or emotional empathy differences in the DCD group.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Personal distress is often considered a maladaptive empathy response associated with depression, rumination, and negative self-image [ 73 , 129 ], and increased personal distress in ASD is consistent with a prior study from our group with lower sample sizes [ 73 ]. As we have already discussed the nuances of empathy in ASD in our previous paper (interactions with alexithymia and interoceptive processing being key modulators to empathy in ASD) [ 73 ], we do not expand on this finding here, only noting that our results here do not show support for cognitive or emotional empathy differences in the DCD group.…”
Section: Discussionsupporting
confidence: 91%
“…The DCD and TD groups did not differ in alexithymia; however, the ASD group scored significantly higher on alexithymia than both groups, consistent with our prior research and that of others [ 68 , 73 ]. To our knowledge, this is the first study to report that children with DCD have scores on alexithymia comparable to those of their TD peers.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Empathy is an important domain of social cognition that is closely associated with poor functioning and suicide in patients with schizophrenia (Smith et al, 2012; Wang et al, 2020, 2021). Specifically, our findings revealed that patients with alexithymia experienced greater difficulty in understanding the thoughts and emotions of others, consistent with previous research conducted in community samples as well as individuals with depression or autism (Banzhaf et al, 2018; Brett & Maybery, 2022; Butera et al, 2023; Yang et al, 2020). These results align with the theory that accurate identification of one's own emotions is vital for perceiving and comprehending the emotions of others (Di Tella et al, 2020).…”
Section: Discussionsupporting
confidence: 91%